Consumer Preferences in Monopolistic Competition Models - Alexander Tarasov (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This paper develops a novel approach to modeling references in monopolistic competition models with a continuum of goods. In contrast to the commonly used CES preferences, which do not capture the effects of consumer income and the intensity of competition on equilibrium prices, the present preferences can capture both effects. I show that under an unrestrictive regularity assumption, the equilibrium prices decrease with the total mass of available goods (which represents the intensity of competition in the model) and increase with consumer income. The former implies that the entry of rms in the market or opening a country to international trade has a pro-competitive effect that decreases equilibrium prices.
urn:nbn:de:bvb:19-epub-11489-8
Keywords: D4; 330; firm prices; intensity of competition; consumer income; Preistheorie; Monopolistischer Wettbewerb; Konsumentenverhalten; Präferenztheorie; Internationaler Wettbewerb; Wohlfahrtsanalyse; Theorie